A Novel Toll-Like Receptor 2 Agonist Protects Mice in a Prophylactic Treatment Model Against Challenge With Bacillus anthracis - Chiang, Chih-Yuan; Lane, Douglas J.; Zou, Yefen; Hoffman, Tim; Pan, Jianfeng; Hampton, Janice; Maginnis, Jillian; Nayak, Bishnu P.; D’Oro, Ugo; Valiante, Nicholas; Miller, Andrew T.; Cooke, Michael; et al. (Frontiers in Microbiology, 2022)
Current therapies for anthrax include the use of antibiotics (i.e. doxycycline, and ciprofloxacin), an anthrax vaccine (BioThrax) and Bacillus anthracis-specific, monoclonal antibody (mAb) based immunomodulators (i.e. Raxibacumab and obiltoxaximab). In this study, we investigated the activity of immunomodulators, which potentiate inflammatory responses through innate immune receptors. The rationale for the use of innate immune receptor agonists as adjunctive immunomodulators for infectious diseases is based on the concept that augmentation of host defense should promote the antimicrobial mechanism of the host. Our aim was to explore the anti-B. anthracis effector function of Toll-like receptor (TLR) agonists using a mouse model. Amongst the six TLR ligands tested, Pam3CSK4 (TLR1/2 ligand) was the best at protecting mice from lethal challenge of B. anthracis. We further benchmarked the activity of a novel TLR2 ligand, DA-98-WW07, with Pam3CSK4. DA-98-WW07 demonstrated enhanced protection in B. anthracis infected mice. The surviving mice that received DA-98-WW07 when re-challenged with B. anthracis 20 days post the first infection showed increased survival rate. Moreover, ciprofloxacin, when treated in adjunct with a suboptimal concentration of DA-98-WW07 demonstrated augmented activity in protecting mice from B. anthracis infection. Taken together, we report the therapeutic potential of DA-98-WW07 for prophylactic treatment for anthrax and the potential utility of immunomodulators in combination with an antibiotic to treat infections caused by the B. anthracis bacterium